Kata Hasad dalam al-Qur’an: Analisis Ayat Hasad dengan Pendekatan Semantik - Nurul Apipah; M. Yusuf Wibisono; Siti Chodijah; Ecep Ismail (Gunung Djati Conference Series, 2022)
This study aims to discuss the word hasad in the Qur'an with a semantic approach. This study uses a qualitative approach by applying the analytical-descriptive method. The formal object of this research is semantics and the material object of this research is the word hasad in the Qur'an. The results and discussion of this study indicate that the word hasad is mentioned four times in the Qur'an with various meanings. This study concludes that the word hasad has the meaning of bad behavior that shows a dislike when seeing other people get pleasure and wants the pleasure to move to him.